Identification and Integrating FSF into Farming Systems to Harness High Potential of FSF for Mountain Agriculture in Nepal - Bhatta, Madan (2018)
Madan Raj Bhatta IFPRI-FAO conference side event, "Accelerating the End of Hunger and Malnutrition" November 28–30, 2018 Bangkok, Thailand